Psychometric Validation of the Passive and Active Use Measure (PAUM) for Facebook and Instagram among a Portuguese Sample - Mendes, Liliana; Leonido, Levi; Pereira, Natercia; Morgado, Elsa (Specijalna edukacija i rehabilitacija, 2025)
Introduction. The advent of social media has fundamentally transformed how people interact, bridging the divide between passive digital consumption and active engagement. Objective. This study aims to validate the Passive and Active Use Measure (PAUM) for Facebook and Instagram in a Portuguese sample, exploring distinct interaction modes encompassing Active Social, Active Non-social, Active, and Passive. Methods. Two descriptive, cross-sectional, and quantitative studies were conducted, involving a total of 606 participants (N=198 for study 1, N=408 for study 2), spanning ages 17 to 67. Results. The factor structure of both scales was analyzed, as well as their convergent and discriminant validity and reliability. Both scales–PAUM-Facebook (study 1) and PAUM-Instagram (study 2)–demonstrated robust factorial structures, underscored by sound validity and reliability indicators. Comprising ten and seven items, respectively, these scales are organized into two dimensions: Active and Passive. Conclusion. This study establishes that the PAUM instruments possess strong psychometric properties, rendering them valuable tools for evaluating Facebook and Instagram usage patterns in Portuguese populations, with broader applicability in future research within the field of psychology.
Keywords: social media; Instagram; Facebook; active use,; passive use; Portuguese sample